PENINGKATAN MUTU BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM MELALUI MEDIA MIND MAPPING DI SMP ISLAM TANFIRUL GHOYYI LAMONGAN - Alanshori, M. Zainuddin; Faiqoh, Faiqoh (Akademika, 2018)
The bachelor thesis entitled "Improving the quality of students in learning the History of Islamic Culture through the media mind mapping (In Islamic Junior High School / SMP Tanfirul Ghoyyi Lamongan) is the result of qualitative research aimed at answering questions on how to improve the quality of students in learning the History of Islamic Culture through media mind mapping, what are the efforts of teachers in improving the quality of students in learning the History of Islamic Culture through the media mind mapping, how are the supporting and inhibiting factors in improving the quality of students in learning the History of Islamic Culture through the media mind mapping. To obtain complete data, this research uses a qualitative approach. In data collection, the writer uses interviews, observation, and documentation. While the data analysis are through data reduction, data presentation and verification. The results showed that improving the quality of students in learning the History of Islamic Culture through the media mind mapping is the quality of student-based active, fun, contemporary learning. The efforts of teachers in improving the quality of students in learning the History of Islamic Culture through the media mind mapping are giving explanations of mind mapping techniques, effective reading techniques to find keywords included in the mind mapping, writing systematic mind mapping techniques. Supporting factors are the availability of mind mapping software, online information technology that provides a variety of inspirations for the preparation of mind mapping, creativity of teachers in making mind mapping, student enthusiasm in making mind mapping; while inhibiting factors are students' difficulties to determine the effective and relevant material that are displayed in the mind mapping, the length of time of learning, and excessive mind mapping presentation.